Quality of regional foods from the cuisine of Paraíba processed by the Sous Vide system (Research, Society and Development, 2022)
The sous vide system is a cooking method in which foods are vacuum packed and subjected to rapid heating and cooling, which can improve palatability, nutritional value and increase the shelf life of foods. This study aimed to evaluate, through microbiological and physicochemical analysis, the use of the sous vide method in typical preparations of the cuisine of Paraíba. The preparations were made using the following ingredients: beef or poultry, rice, tomatoes, onions, peppers, salt and black pepper. After the pre-preparation, which included cuts and addition of seasonings, the ingredients were vacuum packed and subjected to cooking at low temperatures for a long period. After the cooking period, the preparations were immediately and rapidly cooled until they reached 5±0.5°C. Finally, they were stored in refrigeration chambers at 2±1°C for up to 45 days. To evaluate the preparations submitted to the sous vide technique, microbiological and physical-chemical analyzes were performed immediately after processing and after 7, 14, 21, 30 and 45 days. It was found that, after 45 days of cold storage, the preparations were in accordance with the microbiological standards established for mixed preparations. As for the physical-chemical analysis, there was a difference in the color parameters (L*, a* and b*) during the storage time in each analyzed dish. Therefore, it is concluded that mixed preparations produced using the sous vide method are safe for consumption for up to 45 days, with only changes in color characteristics.